A niche for ecosystem multifunctionality in global change research - Darren P. Giling; Léa Beaumelle; Helen R. P. Phillips; Simone Cesarz; Nico Eisenhauer; Olga Ferlian; Felix Gottschall; Carlos Guerra; Jes Hines; Agnieszka Sendek; Julia Siebert; Madhav P. Thakur; et al. (Global Change Biology, 2019)
Concern about human modification of Earth's ecosystems has recently motivated ecologists to address how global change drivers will impact the simultaneous provisioning of multiple functions, termed ecosystem multifunctionality (EMF). However, metrics of EMF have often been applied in global change studies with little consideration of the information they provide beyond single functions, or how and why EMF may respond to global change drivers. Here, we critically review the current state of this rapidly expanding field and provide a conceptual framework to guide the effective incorporation of EMF in global change research. In particular, we emphasize the need for a priori identification and explicit testing of the biotic and abiotic mechanisms through which global change drivers impact EMF, as well as assessing correlations among multiple single functions because these patterns underlie shifts in EMF. While the role of biodiversity in mediating global change effects on EMF has justifiably received much attention, empirical support for effects via other biotic and physicochemical mechanisms are also needed. Studies also frequently stated the importance of measuring EMF responses to global change drivers to understand the potential consequences for multiple ecosystem services, but explicit links between measured functions and ecosystem services were missing from many such studies. While there is clear potential for EMF to provide novel insights to global change research, predictive understanding will be greatly improved by insuring future research is strongly hypothesis‐driven, is designed to explicitly test multiple abiotic and biotic mechanisms, and assesses how single functions and their covariation drive emergent EMF responses to global change drivers.